Approximate Method for Solving the Linear Fuzzy Delay Differential Equations - S. Narayanamoorthy; T. L. Yookesh (Discrete Dynamics in Nature and Society)
We propose an algorithm of the approximate method to solve linear fuzzy delay differential equations using Adomian decomposition method. The detailed algorithm of the approach is provided. The approximate solution is compared with the exact solution to confirm the validity and efficiency of the method to handle linear fuzzy delay differential equation. To show this proper features of this proposed method, numerical example is illustrated.